"We Really Help, Taking Care of Each Other": Older Homeless Adults as Caregivers. (December 2019) - Rosenwohl-Mack, Sarah; Kushel, Margot; Ramsey, Claire; Handley, Margaret; Knight, Kelly R.
Objectives: Many older homeless adults maintain contact with family. We conducted a qualitative study examining the role of family caregiving for older homeless adults. Method: We conducted semi-structured qualitative interviews with a sample of 46 homeless participants who reported spending at least one night with a housed family member in the prior 6 months. Results: A total of 13 of 46 older adult participants provided caregiving. Themes included (a) the death of the care recipient led to the participant's homelessness; (b) feeling a duty to act as caregivers; (c) providing care in exchange for housing; (d) caregivers' ability to stay was tenuous; (e) providing care conflicted with the caregiver's needs; and (f) resentment when family was ungrateful. Discussion: In a sample of older homeless adults in contact with family, many provided caregiving for housed family. For some, caregiving precipitated homelessness; for others, caregiving provided temporary respite from homelessness, and for others, caregiving continued during homelessness.